Molecular Oligomerization and Donor Engineering Strategies for Achieving Superior NIR‐II Fluorescence Imaging and Thermotherapy under 1064 nm Laser Irradiation. Issue 1 (11th November 2022) - Liu, Jiawei; Xiong, Yanwei; Gao, Yicong; Xu, Xingpeng; Chen, Kai; Shen, Qingming; Huang, Wei; Fan, Quli; Wang, Qi
Abstract: An enormous challenge still exists for designing molecules with the second near‐infrared (NIR‐II, 1000–1700 nm) window absorption, NIR‐II fluorescence emission, and batch‐to‐batch reproducibility, which is the premise for high‐performance NIR‐II phototheranostics. Although organic small molecules and polymers have been largely explored for phototheranostics, it is difficult to satisfy the above three elements simultaneously. In this work, molecular oligomerization (the general structure is S‐D‐A‐D′‐A‐D‐S) and donor engineering (changing the donor linker D') strategies are applied to design phototheranostic agents. Such strategies are proved to be efficient in adjusting molecular configuration and energy level, affecting the optical and thermal properties. Three oligomers (O–T, O–DT, and O–Q) are further prepared into water‐soluble nanoparticles (NPs). Particularly, the O‐T NPs exhibit a higher molar extinction coefficient at 1064 nm (≈4.3‐fold of O‐DT NPs and ≈4.8‐fold of O‐Q NPs). Furthermore, the O–T NPs show the highest NIR‐II fluorescence brightness and heating capacity (PCE = 73%) among the three NPs under 1064 nm laser irradiation and served as agents for NIR‐II imaging guided in vivo photothermal therapy. Overall, by using molecular oligomerization and donor engineering strategies, a powerful example of constructing high‐performance NIR‐II phototheranostics for clinical translation is given. Abstract : High‐performance phototheranostic agents with good NIR‐II absorption, NIR‐II fluorescence, and batch‐to‐batch reproducibility are successfully constructed by using molecular oligomerization and donor engineering strategies. The developed O–T nanoparticles (NPs) possessed strong absorption at 1064 nm, excellent NIR‐II fluorescence brightness, and prominent hyperthermia production ability (photothermal conversion efficiency 73%), which display excellent theranostic outcomes.